THE IMPACT OF PHONETIC INTERFERENCE ON ENGLISH PRONUNCIATION IN A SECOND LANGUAGE CONTEXT - Tokimbetova Gulnaz (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines the impact of phonetic interference on English pronunciation in a second language context. Phonetic interference, which occurs when features of a speaker’s native language influence the production of sounds in a target language, remains a significant challenge for language learners. The research aims to identify common pronunciation errors and analyze their underlying phonetic causes.